Students and Artificial Intelligence - Sisca Septiani; Suwito Eko Pramono; Joko Sutarto; Cahyo Budi Utomo (International Conference on Science, Education, and Technology, 2023)
This study aims to conduct a literature study on the influence of Artificial Intelligence (AI) on students. In today's digital age, AI has played an essential role in various aspects of human life, including Education. Students are a group that is directly affected by the development of AI technology. Therefore, this study aims to identify and analyze the impact of AI on students, both in terms of learning, skill development, well-being, and challenges that may be faced. This research uses a literature study approach. Data and information will be collected through literature searches from academic sources and related research related to the use of AI in student education. The relevant data will be systematically analyzed and synthesized to understand this topic comprehensively. This research is expected to provide insight into the influence of AI on college students and provide a better understanding of the benefits, challenges, and implications of using AI in Higher Education. The results of this research can be a foundation for developing better strategies for integrating AI technology in student learning environments. With the increasing presence of AI in Education, it is essential to understand its impact on college students. This literature study will provide a comprehensive overview of the benefits of AI for college students, such as increased access to resources, personalized learning, and technology skills development. However, privacy concerns, ethics, and access inequality also need attention. The results of this research are expected to provide insights for educational institutions to integrate AI wisely and effectively in the student learning experience. A limitation of this study is the reliance on existing literature studies. The study did not include primary data or students' direct experiences related to AI. Therefore, advanced research with different methods, such as surveys or interviews, can be needed to complete the understanding of the influence of AI on college students.